Adaptive Hint Generation for Educational Games Using Fuzzy Logic - Primanita, Anggina; Satria, Hadipurnawan; Rizqie, Muhammad Qurhanul; Iskandar, Ananda Haykel; Nugraha, Wibisena (JURNAL TEKNIK INFORMATIKA, 2025)
The increasing interest in programming education has led to a wide variety of learner abilities. However, existing learning media often remain fragmented, necessitating the development of adaptive tools to cater to learners of varying skill levels. This study employs fuzzy logic to generate dynamic hints for players struggling to solve programming challenges in an educational game. The effectiveness of the system was evaluated through both simulation and real-world experiments. Simulation results indicate that the fuzzy logic system successfully generates personalized hints, with the highest frequency of hints provided to beginner players. Real-world testing using the GUESS-18 framework demonstrated high playability and excellent usability scores for the game.